CONTROLLED REACTANCES IN POWER CONTROL SYSTEMS - Drjuchin, Olexander; Guz, Maksym (Scientific Works of Vinnytsia National Technical University, 2015)
For matching of radio receivers output stages and electric drives it is suggested to use the controlled reactance containing two transistors of opposite type of conductance, the resistor between input and control electrodes is connected, the capacitor is connected to control electrode and common electrode. Third and fourth transistors of the opposite type of conductance, four diodes and two throttle valves are introduced. REFERENCES 1. Патент 67790 Україна, МПК(2012.01) Н ОЗ Н 11/00 / Керована індуктивність / П. О. Гаврасієнко, О. О. Дрючин, А. П. Тульчій.; заявник та патентовласник Вінницький національний технічний університет. – № u 201108327; заявл. 04.07.11 ; опубл. 12.03.12, Бюл. № 5. 2. Радиопередающие устройства / [Шахгильдян В. В., Козырев В. Б., Ляховкин А. А., Нуянзин В. П., Розов В. М., Шумилин М. С.] ; – [2 изд. ]. – Μ.: Радио и связь, 1990. – 432 c. 3. Генерирование колебаний и формирование радиосигналов: Г 34 учеб. пособие / [В. Н. Кулешов, Н. Н. Удалов, В. М. Богачев и др.] ; под ред. В. Н. Кулешова и Н. Н. Удалова. – М.: Издательский дом МЭИ, 2008. – 416 с.